Engineering functional hydrochar based catalyst with corn stover and model components for efficient glucose isomerization. (15th June 2022) - E, Shuang; Jin, Caidi; Liu, Jianglong; Yang, Luhan; Yang, Ming; Xu, Enbo; Wang, Kaiying; Sheng, Kuichuan; Zhang, Ximing
Abstract: The conversion of biomass to functional hydrochar based catalysts for sustainable biorefinery application is critical but still challenging. In this study, mild hydrothermal treatment combined with limited oxygen calcination was developed to treat corn stover and model components for directional preparation of hydrochar based catalysts. The prepared catalysts with various Al active species, exhibited high specific surface area, hierarchical pores, cross-linked carbon microspheres, and excellent catalytic and recycling performances for glucose isomerization. After optimization, a fructose yield of 35.1% (selectivity 77.4%) was obtained at 160 °C for 20 min and it was still more than 25% after the fourth recycling. The reaction kinetics for glucose isomerization was studied. This study established the physicochemical properties-performance relationships of hydrochar based catalysts. The optimized hydrothermal and calcination steps were crucial to improving performance by regulating the active sites and catalyst structures. Moreover, nitrogen, silicon and other elements coupled together could form functional compounds, which is vital for improving the catalytic performance by the synergy between support and Al active center. Three components in corn stover played distinct roles in the catalysis step. This study provides a novel way for developing efficient and recyclable catalysts from biomass, which could be applied in biorefining. Graphical abstract: Image 1 Highlights: Explored mild hydrothermal with limited oxygen calcination to prepare catalyst. The optimized catalyst has excellent catalytic and recycling performances. The reaction kinetics for glucose isomerization was studied. Three model components were tested to further illuminate the reaction mechanism. The key factors affecting the catalytic performance of catalyst were expounded.